2014
DOI: 10.2224/sbp.2014.42.8.1365
|View full text |Cite
|
Sign up to set email alerts
|

Charismatic Leadership and Organizational Citizenship Behavior: the Mediating Role of Ethical Climate

Abstract: We examined the influence of charismatic leadership on ethical climate and organizational citizenship behavior (OCB). Data were obtained from 600 employees in several industry sectors. The findings showed positive relationships among charismatic leadership, ethical climate, and OCB. Ethical climate was found to be a weak mediator in the relationship between charismatic leadership and OCB. However, ethical climate mediated the relationship between the OCB factor of civic virtue and charismatic leadership factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Scholars have focused on the processes of transmission of corporate values from the leader to the follower, as well as on the impact they have on other psychological and organizational variables (Graber and Kilpatrick, 2008;Mancheno et al, 2009). Other studies have examined, instead, styles and types of leadership and their effect on work experiences (Brown et al, 2005;Leung, 2008;Zehir et al, 2014;Dinc and Aydemir, 2014;Newman et al, 2017;Ning and Zhaoyi, 2017;Naeem et al, 2019).…”
Section: The Progressive Distribution Of Leadershipmentioning
confidence: 99%
“…Scholars have focused on the processes of transmission of corporate values from the leader to the follower, as well as on the impact they have on other psychological and organizational variables (Graber and Kilpatrick, 2008;Mancheno et al, 2009). Other studies have examined, instead, styles and types of leadership and their effect on work experiences (Brown et al, 2005;Leung, 2008;Zehir et al, 2014;Dinc and Aydemir, 2014;Newman et al, 2017;Ning and Zhaoyi, 2017;Naeem et al, 2019).…”
Section: The Progressive Distribution Of Leadershipmentioning
confidence: 99%
“…The result revealed that EC positively moderate the relationship between job satisfaction and organizational commitment including the dimensions of JS. Other studies use EC and found positive results (Cheng & Wang, 2014;Öncer & Y ld z, 2012;Zehir, Müceldili, Altinda , ehito lu, & Zehir, 2014).…”
Section: Ec As a Potential Moderator On The Relationship Between Hrm mentioning
confidence: 96%
“…An organisation's ethical culture is significantly related to the presence of OCB (Huang, You, & Tsai, ; Ruiz‐Palomino & Martinez‐Canas, ). Ethical climate has been found to mediate the relationship between leadership and OCB in that the leader must be charismatic to motivate employees to follow ethical guidelines and policies; charisma is a component of transformational leadership that is positively related to OCB (Zehir, Müceldili, Altindag, Sehistoglu, & Zehir, ). Randhawa and Kaur (), argue that OC plays an important role in the presence of OCB.…”
Section: Antecedentsmentioning
confidence: 99%
“…Transformational leadership is described as affecting employee behaviour through influence, motivation, stimulation, and consideration of each individual (Irshad & Hashmi, 2014;Lee et al, 2013). Transformational leaders are described as agents of change with charisma and emotional intelligence (Irshad & Hashmi, 2014;Zehir et al, 2014). Empowering employees may decrease burnout and foster OCB (Gilbert, Laschinger, & Leiter, 2010).…”
Section: Organisational Citizenship Behaviour and Leadershipmentioning
confidence: 99%